The Impact of Green Finance on Carbon Emission--Analysis Based on Mediation Effect and Spatial Effect - Guo, Chang-Qing; Wang, Xin; Cao, Dan-Dan; Hou, Yong-Guang (Frontiers in Environmental Science, 2022)
As a microcosm of implementing the ecological civilization construction，carbon emission reduction is a crucial link of accomplishing Eco-friendly development and establishing beautiful China.This paper takes 11 provinces and cities in the Yangtze River Economic Belt from 2006 to 2019 as the research object. Then, the Spatial Durbin Model(SDM) is applied to empirically analyze the temporal and spatial impact of green finance on carbon emission reduction. The findings of study show that: (1) It is the Yangtze River Economic Zone that has exist a significant spatial effect of reducing Carbon dioxide emission, and the various provinces have shown mutual restraint effects of carbon intensity. (2) Green finance has a prominent inhibiting direct effect on carbon intensity, but the indirect effect and the spillover effect of green finance on neighboring provinces are seemingly insignificant; (3) Technological innovation has obvious restraining effect on carbon emission reduction, the direct effect is significantly negative, and the indirect effect is not significant.The industrial structure has a synergistic promotion effect on carbon intensity in the early stage and a synergistic inhibitory effect in the later period. the urbanization has not a significant inhibitory effect on carbon intensity in space. The level of opening to the outside world has a significant inhibitory effect on carbon intensity in space.